Household Consumption Through Recent Recessions - Thomas F. Crossley; Hamish Low; Cormac O'Dea (Koç University-TÜSİAD Economic Research Forum (ERF), 2011)
This paper examines trends in household consumption and saving behaviour in each of the last three recessions in the UK. The 'Great Recession' has been different from those that occurred in the 1980s and 1990s. It has been both deeper and longer, but also the composition of the cutbacks in expenditure differs, with a greater reliance on cuts to nondurable expenditure than was seen in previous recessions, and the distributional pattern across individuals differs. The young have cut back expenditure more than the old, as have mortage holders compared to renters. By contrast, the impact of the recession has been similar across education groups. We present evidence that suggests that two aspects of fiscal policy in the UK in 2008 and 2009 - the temporary reduction in the rate of VAT and a car scrappage scheme - had some success in encouraging households to increase durable purchases.
Keywords: E21; D12; 330; Consumption; Spending; Recessions; Konjunktur; Privater Konsum; Sparen; Privater Haushalt; Finanzpolitik; Haushaltseinkommen; Großbritannien